Humor, Communication Satisfaction And Organizational Citizenship Behavior In Iranian Electrical Manufacturing Industry - Al-Eslami Kandlousi, Nader Sheykh (2010)
The purposes of the present study were to: (I) to study the relationship between Iranian employees' communication dimensions with their communication satisfaction at the work place, (2) to examine the relationship between Iranian employees' humor with their communication satisfaction at the work place, and (3) to assess the relationship of employees' communication satisfaction with their OCB. Kajian ini bertujuan: (I) mengkaji perkaitan di antara dimensi komunikasi pekerja Iran dengan kepuasan komunikasi di tempat kerja, (2) menyelidik perkaitan di antara humor pekerja Iran dengan kepuasan komunikasi di tempat kerja, dan (3) menilai perkaitan kepuasan komunikasi pekerja dengan OCB.